2011
DOI: 10.1002/hec.1706
|View full text |Cite
|
Sign up to set email alerts
|

Demand, selection and patient outcomes in German acute care hospitals

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…53,54 Thirty studies analyzed the association between capacity strain and mortality. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][32][33][34][35][36][37][38][39][40][41][42][43]48,49,53 All observational studies were cohort studies; all but four were retrospective. 32,42,43,46 Eight studies described interventions to improve care during times of capacity strain, [55][56][57][58][59][60][61][62] none using randomization to assign treatment category.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…53,54 Thirty studies analyzed the association between capacity strain and mortality. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][32][33][34][35][36][37][38][39][40][41][42][43]48,49,53 All observational studies were cohort studies; all but four were retrospective. 32,42,43,46 Eight studies described interventions to improve care during times of capacity strain, [55][56][57][58][59][60][61][62] none using randomization to assign treatment category.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies examined hospital mortality as the outcome of interest, while others used ICU 14,22,40 or timespecific mortality. [34][35][36]42,53 There was a statistically significant increase in mortality during times of capacity strain in 18 of 30 studies and in 9 of 12 studies in ICU settings (Table 1). While two studies reported over five-fold mortality associated with capacity strain, 13,43 several studies found more modest 50-150% increases in mortality.…”
Section: Association Between Capacity Strain and Mortalitymentioning
confidence: 96%
See 2 more Smart Citations
“…None of the aforementioned studies in the United States explicitly examined surge circumstances related to an MCI or disaster. A separate study of patient outcomes in German acute care hospitals during an “unexpected” surge in demand for resources (not in the context of an MCI) found longer hospital LOS, but no effect on emergency readmission or mortality for inpatients during the period of excess demand 17 …”
mentioning
confidence: 97%